Tracheobronchomegaly associated with tracheobronchopathia osteochondroplastica: a case report - Li, Zhen Hua; Kong, Lu-Xia; Zhu, Shan; Hu, Yi; Gao, Shan (Frontiers in Medicine, 2024)
The condition of tracheobronchomegaly (TBM) is a rare occurrence characterized by the dilatation of the trachea and bronchi due to severe atrophy of elastic fibers, accompanied by thinning of the muscularis and the development of diverticula between cartilaginous rings. The etiology remains unclear.Tracheobronchopathia osteochondroplastica (TO) is another uncommon airway disease with an unknown etiolog.The co-occurrence of the two diseases has not been reported.Herein, we report and discuss a case involving an elderly man with TBM and TO who has a history of recurrent pneumonia over the past 6 years.